POTENSIAL AIR PADA TURGOR LOSS POINT TUMBUHAN HUTAN GAMBUT DALAM KONDISI STRES GENANGAN DIKAWASAN SUNGAI SEBANGAU, KALIMANTAN TENGAH - B. P Naiola (Research Center for Biology-Indonesian Institute of Sciences, 2000)
Water is one of the main phenomenons dominating the life cycle of biodiversity components in tropical peat land area in Central Kalimantan. However, the exist of water is no longer as a determinant positive factor in the life of plants in that area; instead, water has became a factor creating other problems i.e. flooding stress. This report deals with study on the physiological aspects of tropical peat land plant species. Three species were used namely tumih (Combretocarpus rotundatus),belangeran (Shorea balangeran) dan ramin (Gonystylus bancatus).Employed Pressure-Volume Curve generated from Pressure Chamber, this study were concentrated on the water potential at turgor loss points(?total ??po)in flooding conditions. It is assumed that (?total ??po)) is important in explaining the adaptation ability of these plants to flooding stress. Results shows that ( ?total ??po)in tumih was (-1,06 MPa), belangeran (-1,53 MPa) and ramin (-1,51 MPa) were not significant different between the three species; thus they had similar ability in responding to flooding stress. However, turgor pressure of these species were significantly different; thus the ratio of each MPa decrease of turgor pressure of each species against their own (?total ??po)were different where tumih (0.73 MPa), balangeran (0,78 MPa) and ramin (0,81 MPa). It is suggested that tumih would reach early turgor loss point than the other two species due to its smaller turgor pressure.Comparisons of (?total ??po)among some tropical species were also presented. Due to the relationship between the three water potential components (total water potential, osmotic potential and turgor pressure),thus (?total ??po)maybe genetically controlled, thus it is worth to encourage for further study on this topic.